From Balance to Performance: The Mediating Effect of Job Satisfaction on Work-Life Balance over Job Performance - Jamin Kun Peng Xia; Louis Yong Yu Lee; Yi Lim Chan; Haoran Cao; Shiyu Cao; Xing Er Cham; Daisy Mui Hung Kee (AIBPM Publisher, 2025)
This study investigates the relationship between work-life balance (WLB), job satisfaction, and in-role job performance among Malaysian employees. WLB is conceptualized as a multidimensional construct encompassing six factors: nature of work, work flexibility, workload, compensation, organizational support, and personal life. Using a quantitative explanatory design, data were collected from 96 full-time employees across various industries in Malaysia through an online survey. The data were analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. The results show that work flexibility (? = 0.122, p .05), workload (? = 0.145, p .01), organizational support (? = 0.148, p .01), and personal life (? = 0.325, p .001) significantly enhance job performance, while compensation (? = 0.251, p .01), organizational support (? = 0.186, p .05), and personal life (? = 0.567, p .001) significantly improve job satisfaction. Job satisfaction also positively influences job performance (? = 0.850, p .001). The models explained 53.3% of the variance in job satisfaction and 77.7% in job performance. These findings validate the mediating role of job satisfaction and highlight the importance of supportive and flexible work environments for improving employee outcomes within Malaysia’s evolving workplace context